Usability evaluation and assessment of a novel emergency department IT system developed using a cognitive systems engineering approach. Issue 1 (June 2014) - Clark, Lindsey N.; Guarrera, Theresa K.; McGeorge, Nicolette M.; Hettinger, A. Zachary; Hernandez, Angelica; LaVergne, David T.; Benda, Natalie C.; Perry, Shawna J.; Wears, Robert L.; Fairbanks, Rollin J.; Bisantz, Ann M.
This paper presents the results of a usability evaluation conducted of an electronic Emergency Department information system (EDIS) prototype that was designed using a cognitive system engineering (CSE) approach. Participants were asked to complete tasks using the EDIS prototype, while thinking aloud about their interactions with the displays. Participants also completed subjective assessments of the system that related to 1) cognitive performance support objectives, 2) usability, usefulness, and frequency of system use, and 3) qualitative feedback. Mean scores were calculated for cognitive performance support objectives as well as usability, usefulness, and frequency of use for each display. Mean scores for all cognitive performance support objectives were six or higher. The mean usability score was five or higher, and the mean usefulness score was six or higher. Displays that provided information on individual patient status had the highest scores. Results from this evaluation regarding positive ratings for the cognitive support objectives provide evidence that CSE design methods can be used to understand the goals and objectives of medical work domains.